The development of Dutch COVID-19 ICU triage guidelines from an institutional work perspective - Broughton, Tamara Christina; Weggelaar-Jansen, Anne Marie; de Graaff, Bert (PLOS ONE, 2023)
Introduction Throughout the COVID-19 pandemic, two ICU triage guidelines were developed in the Netherlands—the Pandemic Guideline and the Guideline Code Black—ostensibly to tackle the threat of absolute care scarcity. Healthcare guidelines are generally based on evidence and prescribe what healthcare professionals should do in certain situations. We used the institutional work perspective, focusing on the human agency to create, maintain, and/or disrupt institutional structures, to study the development of these guidelines and observed that they did a lot more than just offering guidance to healthcare professionals. By including the Actor Network Theory (ANT) perspective on materiality’s agency in our theoretical lens, we show how guidelines, as a materiality—a non-human artefact—interact with human actors and as such shape and are shaped by the social context. Methods 17 online documents were analyzed. This analysis resulted in a timeline of events, which was used to identify key actors in the guideline development process. We included 12 purposely sampled respondents for semi-structured interviews. Interview transcripts were thematically coded. Results During their development, the guidelines played a role in diverse forms of institutional work performed by a variety of stakeholders to: 1) strengthen the medical profession of intensivists; 2) control the medical profession; 3) gain support for the actions needed; and 4) protect the medical profession. In turn, institutional work performed by these stakeholders also shaped the guidelines, indicating the two-sidedness of the interaction between human actors and materiality in the healthcare context. Conclusions This case study shows how guidelines as a materiality and human actors interact and influence each other in multiple ways, resulting in institutional work and thus shaping two institutions: the guidelines and healthcare professions. We found that a materiality does not stand on its own but influences and shapes institutional work in relation to human actors. By studying the development, implementation, and use of the guidelines, we gained more empirical insights into the impact materiality can have on the social context of healthcare and how this can influence existing institutional environments.